Survival in stage IV non-small cell lung cancer patients based on radiation dose to immune cells: a retrospective analysis - Feng, Changxing; Wang, Kang; Hu, Tao; Xu, Fuhao; Li, Li; Yuan, Shuanghu (Frontiers in Oncology, 2026)
BackgroundProgrammed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) immune checkpoint inhibitors combined with chemotherapy represent the standard first-line treatment for stage IV non-small cell lung cancer (NSCLC) without driver mutations. Both concurrent and sequential thoracic radiotherapy (RT) have been shown to improve survival outcomes. This study aimed to evaluate the prognostic significance of the estimated dose of radiation to immune cells (EDRIC) in stage IV NSCLC patients receiving first-line immunotherapy (IT), as well as the predictive performance of EDRIC in combination with inflammatory parameters for overall survival (OS).MethodsThis multicenter retrospective study included 167 stage IV NSCLC patients who received concurrent or sequential RT in addition to IT. Spearman’s rank correlation was applied to assess associations between variables. Kaplan-Meier and Cox regression analyses were used to estimate OS and progression-free survival (PFS). A nomogram model was developed to evaluate the prognostic value of each parameter for OS. Receiver operating characteristic (ROC) curve analysis was performed to compare the predictive performance of the three models.ResultsGTV, PTV, and N staging were positively correlated with EDRIC (r=0.3564, p<0.001; r=0.6012, p<0.001; r=0.2592, p=0.0034), whereas lymphocyte nadir was negatively correlated (r=-0.3776, p<0.001). The Cox regression analyses identified EDRIC, lymphocyte nadir, and ALI as independent prognostic factors for OS (HR = 0.42, p=0.001; HR = 2.93, p=0.001; HR = 3.04, p=0.001). EDRIC was the only independent predictor of PFS (HR = 0.43, p=0.001). The combined EDRIC-lymphocyte nadir-ALI model demonstrated superior performance compared with single-factor models in predicting 2-year and 2.5-year OS in stage IV NSCLC patients. These findings were further confirmed in an external validation cohort.ConclusionsIn the IT era, higher EDRIC is associated with poorer OS and PFS, and the combination of EDRIC, lymphocyte nadir, and Advanced Lung Cancer Inflammation Index (ALI) provides more accurate prognostic assessment of OS than any single parameter alone.